Volumetric capacity enhancement in LiFePO4 cathodes by hot isostatic pressing. (15th March 2021) - Wei, Xuefeng; Zhang, Meng; Miao, Baoji; Liu, Ruixin
Abstract: The efficient manufacture of electrodes with high volumetric capacity is crucial for the rechargeable batteries for application in limited space. Hot isostatic pressing (HIP) of LiFePO4 (LFP) cathodes using a pressure of 240 MPa at 90 C is very effective for enhancing volumetric capacity. After HIP treatment, LFP cathodes can reach a density of 2.62 g cm −3, and achieve a volumetric capacity of 362 mAh cm −3, which is about twice as high as that of the conventional LFP cathodes. Especially, under the drive of isostatic pressure, the electrolyte readily infiltrate the voids among LFP particles, facilitating Li ion diffusion. LFP cathodes with the pre-infiltrated electrolyte exhibit superior rate capability and cycle performance, which maintain a volumetric capacity of 188 mAh cm −3 after 200 cycles at 10 C. Graphical abstract: Image, graphical abstract